Fishermen, farmers, forest change and fire - Dennis, R.A.; Puntodewo, A.; Colfer, C.J.P. (1998)
The recent forest fires in Indonesia have left severe scars on the environment and the economy. Remote sensing and GIS are being integrated and utilized to quantify the effects of the burning on the several local communities in West Kalimantan, Indonesia.